A new species of the genus Phonotimpus Gertsch & Davis (Araneae: Phrurolithidae) from Mexico and the transfer of Gosiphrurus schulzefenai Chamberlin & Ivie to Phonotimpus - Chamé-Vázquez, David; Campuzano, Emmanuel F.; Ibarra-Núñez, Guillermo (Zootaxa, 2021)
Phonotimpus padillai sp. nov. is described on the basis of morphological characteristics of both sexes: males are easily distinguished by the shape of the embolus and females by the shape of the copulatory openings. Additionally, Gosiphrurus schulzefenai Chamberlin & Ivie, 1936 is transferred to the genus Phonotimpus Gertsch & Davis, 1940, based on the redescription of the female and first description of the male, with an update of the diagnosis of this species.